Choline chloride–formic acid mixture as a medium for the reduction of pertechnetates – electrochemical and spectroscopic studies. Issue 3 (5th January 2023) - Połomski, Damian; DiBlasi, Nicole A.; Dardenne, Kathy; Gaona, Xavier; Czerwinski, Kenneth; Chotkowski, Maciej
Abstract : Ionic species containing technetium with an oxidation state lower than +7 are very important for nuclear medicine and industry. Application of new choline-based electrolytes for the reduction of TcO4 - prevents the formation of undesired TcO2 . Abstract : The physicochemical properties of a choline chloride (ChCl) and formic acid (FA) mixture (1 : 2 molar ratio) have been studied over a broad range of temperatures (−140 to 60 °C). Differential scanning calorimetry has shown that the examined system remains in the liquid state at very low temperatures – a glass transition is observed in the range of −125 °C to −90 °C. The kinematic viscosity, ionic conductivity and the width of the electrochemical window determined for this system revealed its beneficial electrochemical properties. This indicates the suitability of ChCl : FA electrolytes in electrochemical measurements. In this non-aqueous electrolyte, electrochemical reduction of Tc(vii ) ions has been studied for the first time. Cyclic voltammetry and chronopotentiometry experiments revealed that the electroreduction of pertechnetates is a multi-path process which leads to the formation of a Tc(iv ) ionic form. X-Ray absorption spectroscopy of the latter revealed its structure as a TcCl6 2− complex.